Early detection of duodenal cancer by upper gastrointestinal‐endoscopy in Lynch syndrome. Issue 12 (7th August 2021) - Vangala, Deepak B.; Ladigan‐Badura, Swetlana; Engel, Christoph; Hüneburg, Robert; Perne, Claudia; Bucksch, Karolin; Nattermann, Jacob; Steinke‐Lange, Verena; Rahner, Nils; Weitz, Jürgen; Kloor, Matthias; Tomann, Judith; et al.
Abstract: Small bowel cancer (SBC) is the malignancy with the highest standardized incidence ratio in Lynch syndrome (LS) patients. Of all SBCs, about 50% are duodenal cancers (DCs), therefore being accessible by esophago‐gastro‐duodenoscopy (EGD) for surveillance. We asked whether early detection of DC is possible for LS patients undergoing surveillance by EGD and if surveillance should be limited to specific subgroups. Data for LS patients with DC were retrieved from the registry of the German Consortium for Familial Intestinal Cancer. Patients undergoing active surveillance by EGDs (surveillance group) were compared to those who did not (nonsurveillance group) regarding tumor stage at diagnosis. Union for International Cancer Control stages I‐IIA were defined as early stage disease and IIB‐IV as advanced stage disease. Statistical analysis was performed using Fisher's exact test. Among 2015 patients with pathogenic variants in any mismatch‐repair‐gene, 47 patients with 49 DCs were identified. In 10% of cases, patients were under 35 years at diagnosis; family and personal tumor history did not correlate with DC diagnosis. Pathogenic germline variants in MSH6, PMS2 or EPCAM were present in 10% of patients. Statistical analysis could be performed on 13 DC patients in the surveillance group and 14 in the nonsurveillance group. Early detection was possible for 71% of patients in the surveillance group and 29% of patients in the nonsurveillance group ( P = .021). Early detection of DC by EGD in LS patients is feasible regardless of family history, mutational status and should start no later than 25 years of age. Abstract : What's new? Although rare in the general population, duodenal cancer is among the malignancies with the highest standardised incidence ratio in patients with Lynch syndrome. Primary tumours in the duodenum are accessible by esophagogastroduodenoscopy, thus offering a surveillance option. However, surveillance data in this patient population is scarce and guideline recommendations are vague and inconsistent across the world. This retrospective analysis of the German Consortium for Familial Intestinal Cancer registry reveals that early detection of duodenal cancer in Lynch syndrome patients by upper gastrointestinal endoscopy is feasible and potentially beneficial regardless of age, personal tumour history, and family history.